First B-HCG predict pregnancy outcome after in-vitro fertilization - de Oliveira, Sofia Andrade; Seguro de Carvalho, Fernanda Silveira; Júnior, Julio Elito (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: About 22% of IVF-conceived pregnancies result in spontaneous abortion. Therefore, it is important to predict the complicated and poor pregnancy outcome. Serum human chorionic gonadotrophin levels after 2 weeks of embryo transfer is a reliable marker to predict the pregnancy outcome in patients of IVF. Objective was to correlate the evolution curve of B-HCG after embryo transfer in assisted human reproduction techniques and the pregnancy outcome. Methods: A prospective and observational study. In patients who underwent embryo transfer, a collection of quantitative B-HCG in 12th day after transfer was made. In patients who had beta-HCG positive value (beta-HCG>5.0 mUI/ml), there were two new collections of beta-HCG 48 hours and 72 hours after the first collection. All results have been filed and all pregnancies were accompanied to the final outcome. Results: It was found that B-HCG values above 139.5 mIU / ml were associated with a good prognosis gestational. Conclusions: Larger studies are needed to improve these findings and give better information regarding the prognostic value of early pregnancy hCG levels.